Telaah Komponen dan Metode Penyusunan Kamus Hifdz al-Mufrodat (Memorizing Vocabularies): Kajian Leksikografi - Anis Nurma Sabila; Abdul Muntaqim Al Anshory (Madah: Jurnal Bahasa dan Sastra, 2023)
As a dictionary used as a guide in PPQ Nurul Huda for 10 years, the 'Hifdz al-Mufrodat Dictionary has never experienced changes or additions that are tailored to user needs. This study aims to evaluate the contents of the dictionary with the aim that the 'Hifdz al-Mufrodat Dictionary can become an interesting and effective learning resource. This study uses library research methods with the research object being the 'Hifdz al-Mufrodat Dictionary. The results of the study show that the 'Hifdz al-Mufrodat (Memorizing Vocabularies)' Dictionary component still has three parts even though it only fulfills a small part of the stated standard component criteria. Regarding the method of compiling the dictionary, this dictionary is compiled using a different system in each chapter. Thus, this dictionary is compiled thematically on a small scale. Taking into account some of the deficiencies and the many components that have not been included in the dictionary, this dictionary should be updated and readjusted to user needs, in this context means PPQ Nurul Huda students and the curriculum that covers them.